Method to Prepare Ternary Methanol Electro-Oxidation Catalysts for Direct Methanol Fuel Cell Applications. Issue 6 (1st January 2017) - Yousaf, Ammar Bin; Mukhtar, B.; Al-Ahmed, Amir; Zaidi, Syed Javaid
Abstract : In this work ternary methanol electro-oxidation catalysts based on mesoporous carbon (MC) were prepared by a novel approach for direct methanol fuel cell applications. Platinum (Pt), ruthenium (Ru) along with oxides of iron, cobalt and nickel were used as the active component in the electrocatalyst. A novel approach was used to prepare Pt-Ru/Fe2 O3 -MC, Pt-Ru/CoO-MC and Pt-Ru/NiO-MC methanol electro-oxidation catalysts by synthesizing high surface area Fe2 O3 -MC, CoO-MC and NiO-MC and then followed by impregnation with Pt-Ru. The synthesized metal oxides and catalysts were characterized using FESEM, BET surface area, FT-IR and XRD. The prepared Fe2 O3 -MC, CoO-MC and NiO-MC showed large pore volume of 0.72–1.46 cm 3 /g and high surface area of 686–1589 m 2 /g, which enabled high dispersion of the Pt-Ru nanoparticles. These catalysts have been tested for methanol electro-oxidation activity by electrochemical techniques. The highest catalyst activity of 12.36 mA/mg has been found for the Pt-Ru/NiO-MC, which is higher than the commercial Pt-Ru/C (E-TEK) catalyst. The measured catalytic activity decreased in the order: Pt-Ru/NiO-MC > Pt-Ru/CoO-MC > Pt-Ru/Fe2 O3 -MC > Pt-Ru/C (E-TEK). In addition, Moreover, these prepared catalyst samples also showed good stability, Moreover, these catalysts are fairly stable, which is similar to the commercial catalyst.